Chronic Administration of the Triazolobenzodiazepine Alprazolam Produces Opposite Effects on Corticotropin-Releasing Factor and Urocortin Neuronal Systems - Skelton, Kelly H. (J Neurosci, 2000)
In view of the substantial preclinical evidence that supports a seminal role of central corticotropin-releasing factor (CRF) neuronal systems in the physiology and pathophysiology of stress and anxiety, it is reasonable to suggest that the anxiolytic properties of benzodiazepines are mediated, at least in part, via regulation of CRFergic function. To begin to test this complex hypothesis, we examined the effects of acute and chronic administration of the triazolobenzodiazepine agonist alprazolam on CRF peptide concentrations, receptor-binding density, and mRNA expression in the CNS. Additionally, we measured mRNA expression for urocortin, a recently discovered neuropeptide that is generally considered to be a second endogenous ligand for CRF receptors. Both acute and chronic alprazolam administration was found to decrease CRF concentrations within the locus coeruleus. Furthermore, chronic alprazolam decreased basal activity of the hypothalamic–pituitary–adrenal axis, CRF mRNA expression in the central nucleus of the amygdala, and CRF(1) mRNA expression and receptor binding in the basolateral amygdala. In marked contrast, urocortin mRNA expression in the Edinger-Westphal nucleus and CRF(2A) receptor binding in the lateral septum and ventromedial hypothalamus were increased. Similar findings of an inverse relationship between the CRF(1) and CRF(2A) receptor systems have been reported in an anxiety model based on adverse early-life experience, suggesting the intriguing possibility that CRF neuronal systems may be comprised of two separate, but interrelated, subdivisions that can be coordinately and inversely regulated by stress, anxiety, or anxiolytic drugs.